Glycomimetic affinity-enrichment proteomics identifies partners for a clinically-utilized iminosugar - Cruz, I; Barry, C; Kramer, H; Chuang, C; Lloyd, S; van der Spoel, A; Platt, F; Yang, M; Davis, B (2013)
Widescale evaluation of interacting partners for carbohydrates is an underexploited area. Probing of the 'glyco-interactome' has particular relevance given the lack of direct genetic control of glycoconjugate biosynthesis. Here we design, create and utilize a natural product-derived glycomimetic iminosugar probe in a Glycomimetic Affinity-enrichment Proteomics (Glyco-AeP) strategy to elucidate key interactions directly from mammalian tissue. The binding partners discovered here and the associated genomic analysis implicate a subset of chaperone and junctional proteins as important in male fertility. Such repurposing of existing therapeutics thus creates direct routes to probing in vivo function. The success of this strategy suggests a general approach to discovering 'carbohydrate-active' partners in biology. © 2013 The Royal Society of Chemistry.